Co-administration of extracellular matrix-based biomaterials with neural stem cell transplantation for treatment of central nervous system injury - Damle, Eshan B.; Morrison, Vivianne E.; Cioma, Jozef; Volic, Milla; Bix, Gregory J. (Frontiers in Neuroscience, 2023)
Injuries and disorders of the central nervous system (CNS) present a particularly difficult challenge for modern medicine to address, given the complex nature of the tissues, obstacles in researching and implementing therapies, and barriers to translating efficacious treatments into human patients. Recent advancements in neural stem cell (NSC) transplantation, endogenous neurogenesis, and in vivo reprogramming of non-neural cells into the neuronal lineage represent multiple approaches to resolving CNS injury. However, we propose that one practice that must be incorporated universally in neuroregeneration studies is the use of extracellular matrix (ECM)-mimicking biomaterials to supply the architectural support and cellular microenvironment necessary for partial or complete restoration of function. Through consideration of developmental processes including neurogenesis, cellular migration, and establishment of functional connectivity, as well as evaluation of process-specific interactions between cells and ECM components, insights can be gained to harness and modulate native and induced neurobiological processes to promote CNS tissue repair. Further, evaluation of the current landscape of regenerative medicine and tissue engineering techniques external to the neurosciences provides key perspectives into the role of the ECM in the use of stem cell-based therapies, and the potential directions future neuroregenerative approaches may take. If the most successful of these approaches achieve wide-spread adoption, innovative paired NSC-ECM strategies for neuroregeneration may become prominent in the near future, and with the rapid advances these techniques are poised to herald, a new era of treatment for CNS injury may dawn.